- #1
- 39
- 0
M a s s - s p r i n g - d a m p e r - s y s t e m.
(sorry about the random apostrophe's in some of the writing, i don't want someone to just google and take my working ><. i don't know if the apostrophe thing works though...)
i have two different methods but i don't think either is right, but close. i don't think there is a anything wrong with my calculations, but my problem is more of the form i need to express my answer in.
i'll try to upload a copy of my handwritten version, to make it easier to read, later tonight
mx" = -kx - cx'
mass = m = 4
Spring constant = k = 1
damp ing constant = c
find the gen'eral solu'tion for the case where the damp'ing cons'tant c = sqrt(7), (under damp ing)
y(t) = Matrix( [y1(t)]
[y2(t)])
in REAL FORM. ( i think the previous line means i have to put it in mtrix form, as two first order e quations)
after subbing in the constants into the equation i had:
4x" = -x - sqrt(7)x'
in a previous section i found the matrix to be
A = ( [0 1]
[-1/4 -sqrt(7)/4] )
solving the equation by using the "auxillary equation" method
( 4*lambda^2 + sqrt(7)*lambda + 1 = 0 )
i found lambda (the eigen values) to be:
lambda1 = -sqrt(7)/8 +3i/8
lambda2 = -sqrt(7)/8 -3i/8
here's where my methods split.
->METHOD I
using the underamping equation:
calling little omega "w", and alhpa "a")
lambda1 = -a + wi
lambda2 = -a - wi
(im not sure what happens to the negative when i sub)
A and B are constants
y = A*cos(wt)*e^(-at) + (B*cos(wt)*e^(-at)
y = A*cos((3/8)t)*e^(-(sqrt(7)/8)t) + (B*cos((3/8)t)*e^(-(sqrt(7)/8)t)
this being my gene'ral equation but it needed to be in m'atrix form
i think i need to take that negative i mentioned before into account and use it in my equation so i have the matrix with one positive and one negative
so it would give me:
y = A*cos((3/8)t)*e^(-(sqrt(7)/8)t) + (B*cos((3/8)t)*e^(-(sqrt(7)/8)t)
method II
there's too much to write for the second method but:
instead of subbing into the underdamping equation, i sub into the general
y = (C1)*(X1)*e^(lambda1*t) + (C2)*(X2)*e^(lambda2*t)
where matrix X is the eigen vector, i found by using the "A" matrix that i stated at the top of my solution attempt: (A - lambda*I) where "I" is matrix identity for a 2x2 matrix.
***([ ] [ ]) matrix, each set of square brackets represents a new column, each comma separates a row****
X1 = [1], [(sqrt(7)/8) - 3i/8])
X2 = [1], [(sqrt(7)/8) + 3i/8])
lambda1 = -sqrt(7)/8 +3i/8
lambda2 = -sqrt(7)/8 -3i/8 (from previous info given)
i subbed all my new found values into the gener'al solution and got:
y = (C1)*([1], [(sqrt(7)/8) - 3i/8])*e^(((sqrt(7)/8) - 3i/8)*t)
+ (C2)*([1], [(sqrt(7)/8) + 3i/8])*e^((-(sqrt(7)/8) - 3i/8)*t)
with the " e's " and their indexes, i then used the rule:
e^(a+ib) = (e^a)(cos(b) + i sin(b))
and then multiplied them into the matrixes beside them, (as i am following a very similar example) making my equation very very messy and complicated.
after this is where i stopped because i became really confused. the first method is my own i worked out using the help of a textbook. the second is a method of a given example which i think needs to be solved the same to this one.
in the example I am using for method two, they only take the first term of the equation to use the "e" rule on, ... after this part, everything falles apart for me and i can't tell left from right...
*im so sorry there's so much to read, i shortened it as much as i could without making it too confusing (i hope)
any help would be really appreciated.
thankyou for taking the time to read this.
(sorry about the random apostrophe's in some of the writing, i don't want someone to just google and take my working ><. i don't know if the apostrophe thing works though...)
i have two different methods but i don't think either is right, but close. i don't think there is a anything wrong with my calculations, but my problem is more of the form i need to express my answer in.
i'll try to upload a copy of my handwritten version, to make it easier to read, later tonight
Homework Statement
mx" = -kx - cx'
mass = m = 4
Spring constant = k = 1
damp ing constant = c
find the gen'eral solu'tion for the case where the damp'ing cons'tant c = sqrt(7), (under damp ing)
y(t) = Matrix( [y1(t)]
[y2(t)])
in REAL FORM. ( i think the previous line means i have to put it in mtrix form, as two first order e quations)
Homework Equations
The Attempt at a Solution
after subbing in the constants into the equation i had:
4x" = -x - sqrt(7)x'
in a previous section i found the matrix to be
A = ( [0 1]
[-1/4 -sqrt(7)/4] )
solving the equation by using the "auxillary equation" method
( 4*lambda^2 + sqrt(7)*lambda + 1 = 0 )
i found lambda (the eigen values) to be:
lambda1 = -sqrt(7)/8 +3i/8
lambda2 = -sqrt(7)/8 -3i/8
here's where my methods split.
->METHOD I
using the underamping equation:
calling little omega "w", and alhpa "a")
lambda1 = -a + wi
lambda2 = -a - wi
(im not sure what happens to the negative when i sub)
A and B are constants
y = A*cos(wt)*e^(-at) + (B*cos(wt)*e^(-at)
y = A*cos((3/8)t)*e^(-(sqrt(7)/8)t) + (B*cos((3/8)t)*e^(-(sqrt(7)/8)t)
this being my gene'ral equation but it needed to be in m'atrix form
i think i need to take that negative i mentioned before into account and use it in my equation so i have the matrix with one positive and one negative
so it would give me:
y = A*cos((3/8)t)*e^(-(sqrt(7)/8)t) + (B*cos((3/8)t)*e^(-(sqrt(7)/8)t)
method II
there's too much to write for the second method but:
instead of subbing into the underdamping equation, i sub into the general
y = (C1)*(X1)*e^(lambda1*t) + (C2)*(X2)*e^(lambda2*t)
where matrix X is the eigen vector, i found by using the "A" matrix that i stated at the top of my solution attempt: (A - lambda*I) where "I" is matrix identity for a 2x2 matrix.
***([ ] [ ]) matrix, each set of square brackets represents a new column, each comma separates a row****
X1 = [1], [(sqrt(7)/8) - 3i/8])
X2 = [1], [(sqrt(7)/8) + 3i/8])
lambda1 = -sqrt(7)/8 +3i/8
lambda2 = -sqrt(7)/8 -3i/8 (from previous info given)
i subbed all my new found values into the gener'al solution and got:
y = (C1)*([1], [(sqrt(7)/8) - 3i/8])*e^(((sqrt(7)/8) - 3i/8)*t)
+ (C2)*([1], [(sqrt(7)/8) + 3i/8])*e^((-(sqrt(7)/8) - 3i/8)*t)
with the " e's " and their indexes, i then used the rule:
e^(a+ib) = (e^a)(cos(b) + i sin(b))
and then multiplied them into the matrixes beside them, (as i am following a very similar example) making my equation very very messy and complicated.
after this is where i stopped because i became really confused. the first method is my own i worked out using the help of a textbook. the second is a method of a given example which i think needs to be solved the same to this one.
in the example I am using for method two, they only take the first term of the equation to use the "e" rule on, ... after this part, everything falles apart for me and i can't tell left from right...
*im so sorry there's so much to read, i shortened it as much as i could without making it too confusing (i hope)
any help would be really appreciated.
thankyou for taking the time to read this.